EXPLORING HOW APPLICANTS' PERSONALITY TRAITS MODERATE THE IMPACT OF EMPLOYER BRANDING ON ORGANIZATIONAL TALENT ATTRACTION - Yu-Min Huang; Yu-Tan Chen; Yi-Ting Wang (PEOPLE: International Journal of Social Sciences, 2026)
In the context of global talent competition, employer branding is crucial for talent attraction. However, existing research has largely overlooked individual differences among job applicants, leading to an incomplete understanding of the interaction mechanisms. To address this research gap, this study aims to construct an integrative conceptual framework to elucidate how job applicants' personality traits moderate the relationship between employer branding and organizational attraction. Grounded in Social Identity Theory and Symbolic Interactionism, this paper, through a systematic review of existing literature and theoretical deduction, argues how the five value dimensions of employer branding (interest, social, economic, development, and application) interact with applicants' personality traits of extraversion and conscientiousness, thereby influencing their organizational identification and pursuit intentions. The contribution of this paper lies in proposing a series of propositions for future empirical examination. This work not only enriches employer branding theory from an individualized perspective but also offers profound theoretical guidance for organizations to formulate more targeted talent attraction strategies.